The Role of Social Media as a Means of Communication and Information for Members of the RA Al Fariq Committee - Irawati, Novica; Helmiah, Fauriatun; Astuti, Bela; Wulandari, Naiyla (Jurnal IPTEK Bagi Masyarakat, 2025)
This Community Service program was carried out to enhance digital literacy and improve the effectiveness of communication and information sharing among members of the RA Al Fariq Committee through the use of social media. The main issues identified were the limited understanding of committee members in utilizing social media effectively, the absence of structured digital communication management, and delays in information dissemination. To address these challenges, the team organized a series of training and workshops covering digital literacy, group management, communication ethics, and the development of Standard Operating Procedures (SOPs) for social media utilization in the school environment. The program involved 20 participants, consisting of teachers and committee representatives. The results indicated a significant improvement in participants’ knowledge, skills, and digital awareness, with post-test scores increasing by more than 50% compared to pre-test scores. Furthermore, internal committee communication became more structured with the establishment of an official WhatsApp group as the main coordination channel. Participants also began exploring other platforms such as Facebook and Instagram to broaden the school’s public outreach. This program not only strengthened the role of social media as a tool for communication and information but also fostered a more responsible, productive, and ethical digital culture within the early childhood education environment.